Penerapan Budikdamber Kreatif sebagai Upaya Edukasi dan Pemberdayaan Masyarakat di Desa Jangkang - M. Hariz Taher; Nur Asiah; Fakhrul Rifqi Hakim; Hana Marieta; Nur Khairunnisak; Rachel Jesika; Ragina Angriani; Qibran Tahta Almaudi; Fiqi Hardiansyah; Alfin Firmansyah; Boby Syahputra; Triana Nadila; Arthania Sinurat (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
The implementation of creative Fish Cultivation in Buckets (Budikdamber) in Jangkang Village aims to increase community understanding regarding the utilization of limited land as an effort for food security and family economic empowerment. This program uses a qualitative approach with a descriptive-explanatory model through stages of socialization, workshops, and trials of catfish adaptation in peat water media. The results of the activity show that the Budikdamber method can be implemented well in local conditions, as evidenced by the successful adaptation of catfish seeds to peat water after liming using dolomite to neutralize the pH. The socialization and workshops conducted received a positive response from the community, marked by increased understanding, enthusiasm, and independent efforts of residents to make Budikdamber. In addition to being a solution to fulfill household food needs, this activity also opens up opportunities for small-scale businesses based on local resources. The implementation of creative Budikdamber in Jangkang Village shows great potential in encouraging food independence, environmental awareness, and strengthening the family economy through simple, environmentally friendly technology.